Studies on storage life, and effect of temperature and pre-sowing seed treatments on germination behaviour and maturity indices in King-chilli (Capsicum spp) - VERMA, VEERENDRA KUMAR; JHA, A K; PATEL, R K; NGACHAN, S V (The Indian Journal of Agricultural Sciences, 2018)
King-chilli (Capsicum spp) is a high value spice crop of the North Eastern India. Although crop is having a great demand in national and international market due to its richness in capsaicin and oleoresin contents, however, it is grown in some pockets of the region on small scale due to specific climatic requirement, poor seed germination and traditional cultivation practices. Keeping these in view, the present investigation was undertaken to study the storage life, effect of temperature and pre-sowing seed treatment on germination behaviour and maturity indices of the crop for seed purpose. The results indicated that seeds of King-chilli remain viable and can be stored up to one year. The maximum seed germination (69.67%) was recorded at first month of the storage and then gradually decreased with increase in storage period with least (0.33%) at the 18 months after storage. The optimum temperature for seed germination was 25-30°C. The synchronous, higher germination (65.67%) and vigorous seedling (1477.58) can be raised by pre-sowing seed treatment with KNO3 (5%) for 24 hr. The seeds of dried pod had shown highest germination (68.77%) and seedling vigour (611.37) when the pods are harvested at fully developed yellow stage. However, seed from red ripe fresh pods with 7 days resting period was found ideal for higher germination and vigour over the seeds from the dried pods. Hence, commercial growers can store the seeds of King-chilli for one year and raise vigour seedlings with maximum germination by pre-sowing seed treatment with KNO3 (5%).